Moderating Effect of Celebrity Endorsements on Media Advertisements and Purchase Intention towards Cosmetic Products in Kathmandu Valley - Ojha, Gaurav (Journal of Business and Management, 2022)
Background: This study examines the moderating effect of celebrity endorsement on the relationship between different media advertisements and consumer purchase intention towards skin and hair care cosmetic products among female customers in Kathmandu Valley. Objectives: The purpose of this study is to evaluate the moderating effect of celebrity endorsements on the relationship between different media advertisements and purchase intention towards skin and hair care cosmetic products. Methods: In this study, primary data has been collected from the respondents using quota sampling and the sample size includes 200 respondents from Kathmandu Valley. This research is an empirical study and for examining the moderating effect of celebrity endorsement between independent and dependent variables, correlation, multiple and moderated regression analysis have been used. Results: The results of this study indicate that the overall impact of different media advertisements is positively and significantly associated with purchase intention. More importantly, the presence of celebrity endorsements in different media advertisements enhances and modifies the relationship between different media advertisements and purchase intention towards cosmetic products. Conclusion: The positive and statistically significant association between media advertisements and purchase intention is moderated by celebrity endorsements regarding cosmetic products. Further, marketing implications of data analysis and findings have been comprehensively elaborated in this study.